ANALYTICAL NETWORK PROCESS BERBASIS KRITERIA MAJEMUK DALAM PEMILIHAN KARYAWAN UNTUK PROMOSI JABATAN - Ruhul Amin (Bahasa Indonesia, 2014)
The development of information technology in the era of rapid globalization causes a decision-makingis very important in determining the decisions that must be taken in dealing with problems in the worldof work. Decisions can be influenced by several aspects, this really influences the speed in takingdecisions by the decision maker, where the decisions have to be quick and accurate. This researchwas made using the Analytical Network Process (ANP). Where is this algorithm do the countingprocess to find the best decision, that is by calculating the value of these criteria and compares themwith the calculation of each possible decision to be taken. This research will be used in assisting thedecision maker in determining which employees are promoted to promotion. Criteria used in promotionin accordance with existing procedures in the PT. Bridgestone Tire Indonesia. From the researchbased Decision Model Multi Criteria In Employee Selection For Promotion Using Analytical NetworkProcess (ANP). Decision Support System will make the right decisions and be flexible with aspectsthat affect these decisions, and generate reports to the decision maker to help the decision maker inmaking decisions.Kata Kunci: Analytical Network Process, ANP, Promosi jabatan, Decision Support System, DSS.